2016
DOI: 10.1007/s10620-016-4404-y
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effect and Intestinal Barrier Protection of HU210 Differentially Depend on TLR4 Signaling in Dextran Sulfate Sodium-Induced Murine Colitis

Abstract: Our study indicates that in experimental colitis, HU210 displays a protective effect on the intestinal barrier function independently of the TLR4 signaling pathway; however, in the extraintestinal tissues, the anti-inflammatory action seems through affecting TLR4-mediated p38 mitogen-activated protein kinase pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The role of TLR4‐related signaling in GB varies according to the specific conditions. In a previous study, we found that TLR4 deficiency improved GB function in colitis . Moreover, Dheer et al .…”
Section: Introductionmentioning
confidence: 66%
“…The role of TLR4‐related signaling in GB varies according to the specific conditions. In a previous study, we found that TLR4 deficiency improved GB function in colitis . Moreover, Dheer et al .…”
Section: Introductionmentioning
confidence: 66%
“…These results are in agreement with a previous study using a similar DSS treatment protocol in WT and Tlr4 −/− mice (24). Some previous studies showed that, compared to WT mice, Tlr4 −/− mice had attenuated DSS-induced colitis (2527), or enhanced colitis (28). These inconsistent results could be in part due to differences in treatment conditions or in mouse strains.…”
Section: Discussionmentioning
confidence: 99%
“…POI increases the risk of postoperative complications and morbidity [ 3 ]. Recent studies have shown that postoperative inflammatory reactions are involved in the development of POI [ 10 , 13 , 14 ]. Consistently, with earlier reports [ 6 , 7 ] at 24 h and 48 h after intestinal manipulation, we observed a significant decrease in the GI transit rate and induction of an inflammatory response characterized by leukocyte infiltration in the intestinal tissue, villous epithelial cell structural damage, submucosal edema, hyperemia, and epithelial cell necrosis.…”
Section: Discussionmentioning
confidence: 99%